Mechanisms of multidrug resistance caused by an Ipi1 mutation in the fungal pathogen Candida glabrata - Taiga Miyazaki; Shintaro Shimamura; Yohsuke Nagayoshi; Hironobu Nakayama; Akihiro Morita; Yutaka Tanaka; Yasuhiko Matsumoto; Tatsuo Inamine; Hiroshi Nishikawa; Nana Nakada; Makoto Sumiyoshi; Tatsuro Hirayama; et al. (Nature Communications)
Abstract Multidrug resistance in the pathogenic fungus Candida glabrata is a growing global threat. Here, we study mechanisms of multidrug resistance in this pathogen. Exposure of C. glabrata cells to micafungin (an echinocandin) leads to the isolation of a mutant exhibiting resistance to echinocandin and azole antifungals. The drug-resistant phenotype is due to a non-synonymous mutation (R70H) in gene IPI1, which is involved in pre-rRNA processing. Azole resistance in the ipi1 R70H mutant depends on the Pdr1 transcription factor, which regulates the expression of multidrug transporters. The C. glabrata Ipi1 protein physically interacts with the ribosome-related chaperones Ssb and Ssz1, both of which bind to Pdr1. The Ipi1-Ssb/Ssz1 complex inhibits Pdr1-mediated gene expression and multidrug resistance in C. glabrata, in contrast to Saccharomyces cerevisiae where Ssz1 acts as a positive regulator of Pdr1. Furthermore, micafungin exposure reduces metabolic activity and cell proliferation in the ipi1 R70H mutant, which may contribute to micafungin tolerance.